Supramolecular Arrangement of Doxycycline with Sulfobutylether-β-Cyclodextrin: Impact on Nanostructuration with Chitosan, Drug Degradation and Antimicrobial Potency - Renata Carvalho Feitosa; Juliana Souza Ribeiro Costa; Marcelo van Vliet Lima; Elina Sawa Akioka Ishikawa; Karina Cogo Müller; Fernando Bonin Okasaki; Edvaldo Sabadini; Claudia Garnero; Marcela Raquel Longhi; Vladimir Lavayen; Arnóbio Antônio da Silva-Júnior; Laura Oliveira-Nascimento (MDPI AG, 2023)
Doxycycline (DX) is a well-established and broad-spectrum antimicrobial drug. However, DX has drawbacks, such as physicochemical instability in aqueous media and bacterial resistance. The inclusion of drugs in cyclodextrin complexes and their loading into nanocarriers can overcome these limitations. Thus, we studied the DX/sulfobutylether-β-CD (SBE-β-CD) inclusion complex for the first time and used it to reticulate chitosan. The resulting particles were evaluated by their physicochemical characteristics and antibacterial activity. DX/SBE-β-CD complexes were characterized by nuclear magnetic resonance, infrared spectroscopy, thermal analysis, X-ray diffraction, and scanning electron microscopy (SEM), whereas DX-loaded nanoparticles were characterized by dynamic light scattering, SEM, and drug content. The partial inclusion of the DX molecule in CD happened in a 1:1 proportion and brought increased stability to solid DX upon thermal degradation. Chitosan-complex nanoparticles measured approximately 200 nm, with a narrow polydispersity and particles with sufficient drug encapsulation for microbiological studies. Both formulations preserved the antimicrobial activity of DX against Staphylococcus aureus, whereas DX/SBE-β-CD inclusion complexes were also active against Klebsiella pneumoniae, indicating the potential use of these formulations as drug delivery systems to treat local infections.